Demographic Factors Influencing Marital Discord Among Married Couples - Adekola Kamil Lasisi (Bisma The Journal of Counseling, 2023)
This study was conducted to establish the demographic factors influencing marital discord among married couples in Ilorin West Local Government Area, Kwara State, Nigeria. The descriptive research design of the ex-post facto type was employed for the study. One hundred and fifty randomly selected married couples were the participants of the study. A self-designed but well-validated instrument titled the Marital Discord Scale (M.D.S) with a reliability coefficient of 0.75 was used to collect the research data. Five null hypotheses were raised and tested in the study. T-test statistical procedure was used to analyze the generated data. The findings of the study indicated that there was no significant difference in the perception of married couples in Ilorin West Local Government Area of Kwara State, Nigeria on marital discord based on gender and religious affiliation. It was also found that there was a significant difference in the marital discord of married couples in Ilorin West Local Government Area, Kwara State, Nigeria based on age and educational qualifications. Based on the findings of this study, recommendations were offered. This includes the fact that marital counsellors should be consulted as a matter of necessity to counsel the intending couples on various compatibilities that could elongate their relationship.